Penerapan Senam Rematik terhadap Tingkat Nyeri pada Lansia dengan Rheumatoid Arthritis di Wilayah Kerja Puskesmas Kartasura - Lucky Aprilia Kusumastuti; Sitti Rahma Soleman (Journal of Educational Innovation and Public Health, 2024)
Background: The elderly are vulnerable to chronic diseases and musculoskeletal issues, such as rheumatoid arthritis, which is characterized by pain in the joints and extremities. This disease can lead to persistent pain, fatigue, and an increased risk of injury. One effective non-pharmacological therapy for reducing joint pain in patients with rheumatoid arthritis is rheumatic exercise, which focuses on maintaining range of motion and physical health. Objective: The objective of this research is to describe the comparison of the final results between two respondents before and after the application of rheumatic exercises. Method: This research uses a case study approach with a descriptive method. Descriptive research aims to present or describe the events observed in society. The application of rheumatic exercises was carried out for 4 weeks with a frequency of once a week for 8 minutes. Result: From this study, a decrease in pain levels was found in both respondents, with N. Y's pain level dropping from 5 to 1 and Ny. Y's from 6 to 2. Conclusion: Rheumatic exercise therapy can reduce pain levels in patients with rheumatoid arthritis. (RA).